Buddhism and American cinema - Whalen-Bridge, John; Storhoff, Gary (SUNY series in Buddhism and American culture, 2014)
John Whalen-Bridge: Some (Hollywood) versions of enlightenment -- Representation and intention. Hanh Ngoc Nguyen and R.C. Lutz: Buddhism and authenticity in Oliver Stone's Heaven and earth -- Eve mullen: Buddhism, children, and the childlike in American Buddhist films -- Jiayan Mi and Jason C. Toncic: Consuming Tibet: Imperial romance and the wretched of holy plateau -- Felicia Chan: Politics into aesthetics: cultural translation in Kundun, Seven years in Tibet and The cup -- Allegories of shadow and light. Jennifer l. McMahon and B. Steve Csaki: Momentarily lost: finding the moment in Lost in translation -- Richard C. Anderson and David A. Harper: Dying to be free: the emergence of "American militant Buddhism" in popular culture -- Karsten J. Struhl: Buddhism, our desperation, and American cinema -- Devin Harner: Christian allegory, Buddhism and Bardo in Richard Kelly's Donnie Darko -- David l. Smith: "Beautiful necessities": American beauty and the idea of freedom -- Postscript -- Gary Gach: Afterword: on being luminous